2010
DOI: 10.1136/emj.2010.091561
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of alcohol-related presentations to emergency departments in rural Australia

Abstract: The prevalence of alcohol-related ED presentations observed was at the lower end of the documented range, probably due to methodological differences and limitations, as well as geographic variation. Despite this, alcohol-related presentations were associated with a substantial impact on the ED. Policies and programs to reduce the impact of alcohol on rural emergency departments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…In relation to alcohol, the current study is in accordance with the findings in a recent Australian study on alcohol-related presentations to emergency departments in rural Australia where 9% of presentations were identified as alcohol related [16]. In a review of a number of studies of emergency departments, it was found that victims of violence more often were under the influence of alcohol than other patients presenting at emergency departments [17].…”
Section: Discussionsupporting
confidence: 91%
“…In relation to alcohol, the current study is in accordance with the findings in a recent Australian study on alcohol-related presentations to emergency departments in rural Australia where 9% of presentations were identified as alcohol related [16]. In a review of a number of studies of emergency departments, it was found that victims of violence more often were under the influence of alcohol than other patients presenting at emergency departments [17].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have investigated broad individual correlates of high risk alcohol use including age, gender and socio-economic status [8], yet the geographic variation in rates suggest a potential contribution of district-level factors on patterns of alcohol use. District-level factors that may characterise rural and remote communities include socio-economic disadvantage, greater rates of population change, environmental adversity, and remoteness from services/population centres [9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, 26% of people aged 14 years or older consumed five or more standard drinks on a single drinking occasion at least once a month, placing them at risk of an alcohol‐related injury 2, 3. With an estimated 4–14% of emergency department (ED) presentations in Australia involving excessive alcohol consumption, depending on the time of the week, the ED remains a key setting in responding to alcohol harms 4, 5, 6. Such harms range from acute intoxication and poisoning to life‐threatening events due to intoxication (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Australia, this remains a challenge, as it is not mandatory to screen for or collect data on alcohol‐related ED presentations 4. Typically, the policy response relies on research from cross‐sectional or longitudinal survey‐based studies to estimate the prevalence of alcohol‐related ED presentations 4, 5, 7, 8. However, these study designs can be costly, are limited in their generalisability and are not timely enough to result in changes to service delivery.…”
Section: Introductionmentioning
confidence: 99%